Surface expression of CD11b, CD62L, CD44 receptors on blood and milk neutrophils during subclinical and clinical mastitis in Sahiwal cows - SWAIN, DILIP KUMAR; KUSHWAH, MOHAR SINGH; KAUR, MANDHEER; MOHANTY, ASHOK K; DANG, AJAY K (The Indian Journal of Animal Sciences, 2016)
Surface expression of cell adhering molecules and CD44 was studied in Sahiwal (SW) cows suffering naturally from subclinical (SCM) and clinical mastitis (CM). Cows were divided into groups, viz. healthy (12), SCM (12) and CM (12) groups on the basis of CMT scoring, bacteriological culture, gross morphological changes in the milk and by counting milk SCC after screening of 136 SW cows. Bacteriological culture indicated infection of Staphylococcus aureus as the causative agent of SCM and CM. Healthy cows showed significantly higher CD62L expression as compared to the SCM and CM group of animals in both blood and milk neutrophils but no significant difference was found between blood and milk neutrophils. The results revealed a significant upregulation of CD11b positive cells in the CM group of cows. Significantly higher expression of CD44 was found in the neutrophils of both blood and milk of SCM group as compared to CM group. From the study, it was evident that neutrophils exhibit dynamic interplay between the integrins (CD11b) and selectins (CD62L) along with CD44 during SCM and CM Staphylococcal mastitis to offer host protection against the foreign invaders.